Corporate governance and trade credit: International evidence from board reforms - Cumming, Douglas J.; DeLisle, R. Jared; Lei, Jin; Yang, Zi (Journal of Corporate Finance, 2026)
Drawing on current literature, this study develops a simple external financing model and provides international evidence of the causal effects of corporate governance improvements on trade credit. We introduce an internal governance perspective, hypothesizing that weak internal governance, which fosters managerial agency problems, allows firm managers to misuse trade credit. Specifically, poor governance may lead firms to rely on supplier financing as a substitute for traditional financing when they face financing constraints, a practice the literature argues raises concerns about shifting a firm's financial burdens onto its suppliers. Using a decade of data surrounding governance-enhancing board reforms in 38 countries, our difference-indifferences analyses strongly support these predictions. We find that strengthening board oversight via exogenous reforms reduces firms' reliance on supplier financing. Improved internal governance decreases firms' dependence on supplier financing and limits the manipulation of payables through real earnings management activities, such as inventory overproduction, which affects accounts payable. We also find that the effect of internal governance reforms is most pronounced in countries with stronger external governance mechanisms, suggesting a complementary effect. Additionally, our findings show that enhanced governance leads to better investment decisions and improved firm performance, especially for financially constrained firms and those with high agency costs.